Miguel Rodríguez-Pantoja, Epigrafía latina en verso, Madrid, Akal, 2020, 762 pp. ISBN: 978-84-460-4826-8 - López-Maroto Quiñones, Sara (De Medio Aevo, 2020)
Reseña de la obra de Miguel Rodríguez-Pantoja, Epigrafía latina en verso, Madrid, Akal, 2020, 762 pp. ISBN: 978-84-460-4826-8